PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN TEKNOLOGI INFORMASI TERHADAP PENERAPAN AKUNTANSI BERBASIS AKRUAL PADA PENGELOLAAN BARANG MILIK NEGARA - Intan Puspitarini; Amrie Firmansyah; Dian Handayani (Pusat P2M Politeknik Negeri Batam, 2017)
This research is aimed to examine the association of human resources’ competencies and information technology on the implementation of government accrual based accounting on the state assets management. As mandated by Government Regulation No. 71 of 2010 concerning Government Accounting Standard, the Government of the Republic of Indonesia should prepare its financial reports based on accrual accounting by 2015. This study examines the practice of implementation of accrual accounting in the management and administration of state asset. The examination conducted in this study is different from previous studies which gave more highlight on the preparation and the implementation of accrual accounting in general, while this stud y gives more focus on one specific object in accrual accounting, that is state assets. This study conducts survey by using questionnaires which are then distributed to units in line ministries and government that responsible in managing state assets. 250 questionnaires were distributed to 16 line ministries and 3 government institutions, 234 of those were successfully returned. From the questionnaires returned, 188 are considered valid. The result ot the study shows that the competence of human resources is associated with the application of accrual accounting on government assets. While, the information technology has different result, it is not associated with the application of accrual accounting on government assets. Keywords: accrual accounting, government assets